Data envelopment analysis implementation in producing the projection of inefficient IT projects - Ku-Mahamud, Ku Ruhana; Abd Ghani, Nor Farzana; Ahmad, Faudziah; Mat Kasim, Maznah; Abdullah, Fader (2011)
The efficient utilization of input such as labor, raw material and capital is the main target for organization to produce output such as profit and revenue.The result of this practice will eliminate waste, increase output and increase organization's profit.In order to explore the utilization of input to produce better output, a set of data consists of 39 completed projects in an IT organization were analyzed using Data Envelopment Analysis. Through the projection of inefficient projects both in input and output orientation, it shows that the projects that are not efficient need to be compared with efficient projects to improve the efficiency score.This paper also suggests on the improvements of the inefficient projects by referring on both input and output orientation.It was concluded for an organization to improve their performance, they need to balance the input utilization with output produced.